Marketing Strategy Analysis of Domba Reborn Car Wash Salatiga Using the TOWS MATRIX Method - Ariel Putra Umbu Saga Ludjuwara; Penidas Fiodinggo Tanaem (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2026)
This study is motivated by the increasing competition in the car wash service industry in Salatiga and the suboptimal implementation of digital marketing strategies at Domba Reborn Car Wash. This study aims to analyze and formulate appropriate marketing strategies to improve business competitiveness. The method used is a qualitative descriptive approach with a case study. Data were collected through interviews, observations, and documentation. The data analysis technique was conducted by identifying internal factors (strengths and weaknesses) and external factors (opportunities and threats), which were analyzed using the TOWS Matrix method. The results indicate that the business has strengths in social media utilization, supporting facilities, and additional services. However, weaknesses include limited human resources, suboptimal marketing strategies, and low brand awareness. Opportunities arise from the increasing number of vehicles, while threats come from competitors. Recommended strategies include optimizing digital promotion, improving service quality, developing consistent content strategies, and creating customer loyalty programs. Keywords: marketing strategy, digital marketing, TOWS Matrix, SMEs, car wash service